Linear and Non-Linear Subsidies - David Allan Vardy (Queen's University, Department of Economics, 1971)
This paper focuses upon the theory of subsidies and here the emphasis is not symmetric with the analysis of taxation.While there exists a strong justification for attention given to the financing of government expenditure at minimal distortion cost there are few governments confronted with the problem of deciding how to get rid of excess revenue acquired at zero cost.
Keywords: 330